Keyakinan Keagamaan dalam Konflik antarsukubangsa - Parsudi Suparlan (Antropologi Indonesia, 2001)
This article attempts to show that in the bloody conflicts between ethnic groups, individual ethnic patterns that are individually owned become categorical patterns. No longer are individuals the targets for the ethnic groups in conflict, but rather the categories with the attributes of each ethnic group in conflict. Thus, the attack upon categories based upon their characteristic do no take into account the sex, age or social position of the people displaying these characteristic as attributes of their ethnicity. This article also attempts to show that in each bloody ethnic group conflict, religious beliefs may permeate. Ethnic group conflicts can therefore change (or be made to change)into religious conflict between adherents of different beliefs. However, this does not mean that every ethnic conflict will change into a religious conflict. On the one hand, the religious beliefs of actors in an ethnic conflict serve to reinforce ethnicity and the spirit for eradicating the ethnic category that is the enemy. On the other hand, the religious beliefs of actors dominate ethnicity and take over the latter's function in the effort to eradicate the religious categories of the enemy. Thus, ethnic conflict changed into religious conflict. This essay uses cases from early riots in Ambon, the Sambas riot in West Kalimantan, and the case of Dayak-Madura in Central Kalimantan.